Generation and characterization of DSPP‐Cerulean/DMP1‐Cherry reporter mice. Issue 10 (4th July 2019) - Vijaykumar, Anushree; Ghassem‐Zadeh, Sean; Vidovic‐Zdrilic, Ivana; Komitas, Karren; Adameyko, Igor; Krivanek, Jan; Fu, Yu; Maye, Peter; Mina, Mina
Summary: To gain a better understanding of the progression of progenitor cells in the odontoblast lineage, we have examined and characterized the expression of a series of GFP reporters during odontoblast differentiation. However, previously reported GFP reporters (pOBCol2.3‐GFP, pOBCol3.6‐GFP, and DMP1‐GFP), similar to the endogenous proteins, are also expressed by bone‐forming cells, which made it difficult to delineate the two cell types in various in vivo and in vitro studies. To overcome these difficulties we generated DSPP‐Cerulean/DMP1‐Cherry transgenic mice using a bacterial recombination strategy with the mouse BAC clone RP24‐258g7. We have analyzed the temporal and spatial expression of both transgenes in tooth and bone in vivo and in vitro. This transgenic animal enabled us to visualize the interactions between odontoblasts and surrounding tissues including dental pulp, ameloblasts and cementoblasts. Our studies showed that DMP1‐Cherry, similar to Dmp1, was expressed in functional and fully differentiated odontoblasts as well as osteoblasts, osteocytes and cementoblasts. Expression of DSPP‐Cerulean transgene was limited to functional and fully differentiated odontoblasts and correlated with the expression of Dspp . This transgenic animal can help in the identification and isolation of odontoblasts at later stages of differentiation and help in better understanding of developmental disorders in dentin and odontoblasts.